The Influence of Organizational Culture, Organizational Commitment and Leadership Style on Employee Performance at the Population and Civil Registration Service of Buleleng Regency - I Ketut Sudarnaya; Kadek Pebi Sudarmi (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This research aims to analyze the influence of organizational culture, organizational commitment, and leadership style on employee performance at the Buleleng Regency Population and Civil Registration Service. The research used a quantitative approach involving 95 employees as respondents. Data was collected through questionnaires and analyzed using multiple linear regression. The research results show that organizational culture, organizational commitment, and leadership style each have a positive and significant effect on employee performance. Simultaneously, these three variables also have a significant effect on employee performance with an F-value of 63.487 and a significance of 0.000. The coefficient of determination (R2) value of 0.677 indicates that 67.7% of the variation in employee performance can be explained by organizational culture, organizational commitment, and leadership style, while 32.3% is influenced by other factors outside the research. These findings indicate that strengthening organizational culture, increasing organizational commitment, and implementing an effective leadership style are important factors in improving employee performance.